2003
DOI: 10.1021/bi035001t
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Binding of Hsp90 Is Triggered by Multiple Discrete Segments of Its Kinase Clients

Abstract: The 90 kDa heat shock protein (Hsp90) cooperates with its co-chaperone Cdc37 to provide obligatory support to numerous protein kinases involved in the regulation of cellular signal transduction pathways. In this report, crystal structures of protein kinases were used to guide the dissection of two kinases [the Src-family tyrosine kinase, Lck, and the heme-regulated eIF2alpha kinase (HRI)], and the association of Hsp90 and Cdc37 with these constructs was assessed. Hsp90 interacted with both the N-terminal (NL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
57
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 99 publications
11
57
1
Order By: Relevance
“…Furthermore, the domain structure of Cdc37 has been determined, and its kinase binding and Hsp90 binding activities have been mapped to its N-terminal and middle domains, respectively (20 -22), and we have demonstrated that phosphorylation of Cdc37 at Ser 13 by casein kinase II is require for the ability of Cdc37 to bind protein kinase (23). However, although the specific basis for the recognition of protein kinases by Cdc37 is unknown, recent studies have mapped the recognition motif to the N-terminal lobe of the catalytic domain of protein kinases (12,24,25).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Furthermore, the domain structure of Cdc37 has been determined, and its kinase binding and Hsp90 binding activities have been mapped to its N-terminal and middle domains, respectively (20 -22), and we have demonstrated that phosphorylation of Cdc37 at Ser 13 by casein kinase II is require for the ability of Cdc37 to bind protein kinase (23). However, although the specific basis for the recognition of protein kinases by Cdc37 is unknown, recent studies have mapped the recognition motif to the N-terminal lobe of the catalytic domain of protein kinases (12,24,25).…”
mentioning
confidence: 98%
“…Analyses with these compounds, with nucleotides and nucleotide analogs, and with site direct mutants that alter Hsp90 ATP binding and/or ATPase activity have revealed that Hsp90 function is regulated via the binding and hydrolysis of ATP, which modulates the switching of Hsp90 between at least three alternative conformations (1)(2)(3)(4)32). In the presence of geldanamycin, Hsp90 binds weakly to client kinases in a salt-labile fashion (20,24,33). These aberrant Hsp90 heterocomplexes indicate that nucleotide modulation of conformational switching is required to generate high affinity interactions of Hsp90 and Cdc37 with protein kinases (20,24,33).…”
mentioning
confidence: 99%
See 3 more Smart Citations